A Igreja Universal do Reino de Deus em Angola: faces da nova cartografia religiosa global - Anaxsuell Fernando Silva; Karen Susan Silva Pititinga Rosa (Ciências Sociais Unisinos)
The Universal Church of the Kingdom of God was established in Angola since 1992, but its presence in the country has become uncertain from an unusual episode: in December 2012, in a vigil to the end of the year, 6 people were killed and 120 were injured. This scenario triggered a set of facts and political speeches regarding this religious institution, which questioned the influence of the UCKG in that country. This communication proposal takes this historical fact as an analytical motto to understand the performance of the Brazilian Pentecostal churches in Africa, in particular the Universal Kingdom of God Church in Angola. We aim to question whether that presence should be understood an an instrument that promotes Brazilian imperialism in that country, interfering with the traditional habits of the Angolan culture or, whether, from another perspective, this religious presence should be seen as an agent of integration between Brazil and Angola. In order to conduct the analysis, we start from the reports about the episode in question and go forward with the theoretical and methodological aid of sociology, anthropology and international relations.